Biotelemetry reveals migratory behaviour of large catfish in the Xingu River, Eastern Amazon - Hahn, Lisiane; Martins, Eduardo G.; Nunes, Leonardo D.; da Câmara, Luís Fernando; Machado, Leonardo S.; Garrone-Neto, Domingos [UNESP] (Springer Nature, 2019)
We used a combination of radio and acoustic telemetry to assess the movements of large catfish (Pimelodidae) in the Xingu River, a clearwater tributary of the Amazon River in Brazil. A total of 121 Phractocephalus hemioliopterus and 61 Pseudoplatystoma punctifer were tagged for monitoring within a 685 km segment, including the Belo Monte Hydroelectric Complex (BMHC), between February 2013 and July 2015. Long distance upstream movements were detected for P. hemioliopterus (up to 347 km) and for P. punctifer (up to 164 km) mainly during the transition between dry season and the rising water period. Both species moved through a long segment of rapids previously thought to function as barriers to migration. Several individuals exhibited long-distance bidirectional movements. Some tagged fish never left the release zone, indicating mortality, tag loss or resident individuals, which would characterize partial migration. The findings show evidence of migratory behaviour for large catfish within the Xingu River, emphasizing the influence of the hydrologic cycle on their movements. As part of the study area has become partially dewatered due to the BMHC, findings support the need of adequate management strategies to allow the movements of large catfish between spawning and feeding sites in the Xingu River.